Revealing hidden variability in PWNe with spectral index maps. Issue 1 (17th August 2020) - Guest, Benson T; Safi-Harb, Samar
ABSTRACT: Pulsar wind nebulae (PWNe) are the synchrotron bubbles inflated by the rotational energy of a neutron star. Observing variability within them has previously been limited to cases of significant brightening, or the few instances where transient features are interpreted in terms of intrinsic motion or associated with variability from the pulsar. Jet and torus morphology are also only visible in cases of differing brightness with respect to the surrounding nebula and favourable alignment with our line of sight. Spectral map analysis involves binning observations with an adaptive algorithm to meet a signal limit and colouring the results based on the desired model parameter fits. Minute changes in spectral index become therefore apparent even in cases where brightness images alone do not suggest any underlying changes. We present a Chandra X-ray study of the PWNe in G21.5–0.9, Kes 75, G54.1+0.3, G11.2–0.3, and 3C 58, using archival observations accumulated over the ∼20-yr lifetime of the mission. With the spectral map analysis technique, we discover evidence for previously unknown variability opening a new window into viewing PWNe.